Réponses

  • Utilisateur Brainly
2014-03-09T18:50:48+01:00
1. ( 3x - 2)²=9x²-12x+4
2. ( 7x - 3) (7x + 3) =49x²-9
3. ( 4x +5)² + (3x - 4)²=16x²+40x+25+9x²-24x+16=25x²+16x+41
4. (2x - 1) (2x + 1)
=4x²-1
2014-03-09T18:54:21+01:00
Salut :)

1. ( 3x - 2)²
(3x)² - 2 x 3x x 2 + 2²
9x² - 12x + 4

2. ( 7x - 3) (7x + 3)
(7x)² - 3²
49x² - 9

3. ( 4x +5)² + (3x - 4)²
((4x)² + 2 x 4x x 5 + 5²) + ((3x)² - 2 x 3x x 4 + 4²)
16x² + 40x + 25 + 9x² - 24 + 16
25x² - 16x + 41

4. (2x - 1) (2x + 1)
(2x)² - 1²
4x² - 1

J'espère t'avoir aidé(e)! :)